Teaching negotiation in a globalised world: Benefits of a genre approach - Otilia Hutiu (Peoples' Friendship University of Russia (RUDN University), 2017)
The paper presents a genre-based approach to the study of negotiation within EAP classes and reports on results obtained using a negotiation model meant to increase students' awareness of the generic features of this communicative activity. The model is based on the Pragma-dialectical theory of argumentation offering a double perspective on argumentation discourse, namely a descriptive and normative perspective. The paper, based on desk and field research, aims to help business language students improve their argumentation and negotiation skills by developing discourse skills beyond a simple stage by stage negotiation strategy. To do so it examines the advantages and disadvantages of traditional teaching of negotiation skills and introduces the Pragma-dialectical theory of negotiation developed by van Eemeren and Grootendorst at the University of Amsterdam. The author demonstrates how the practical application of this approach has improved the performance of MA students in Romania.